Association between syndecan-4 and subclinical atherosclerosis in ankylosing spondylitis - Sertdemir, Ahmet L.; Şahin, Ahmet T.; Duran, Mustafa; Çelik, Mustafa; Tatar, Sefa; Oktay, İrem; Alsancak, Yakup (Medicine (Baltimore), 2024)
Background: Despite advances in the diagnosis and treatment of ankylosing spondylitis (AS), the risk of cardiovascular complications in AS patients is still higher than in the general population. Macrophages are at the intersection of the basic pathogenetic processes of AS and atherosclerosis. Although syndecan-4 (SDC4) mediates a variety of biological processes, the role of SDC4 in macrophage-mediated atherogenesis in AS patients remains unclear. Herein, we aimed to investigate the role of SDC4 in subclinical atherosclerosis in AS patients. Methods: Subjects were selected from eligible AS patients and control subjects without a prior history of AS who were referred to the rheumatology outpatient clinics. All participants' past medical records and clinical, and demographic characteristics were scanned. In addition, carotid intima-media thickness (CIMT) measurement and disease activity index measurement were applied to all patients. Results: According to our data, serum SDC4 level was significantly higher among AS patients compared with the control group (6.7 [1.5-35.0] ng/mL vs 5.1 [0.1-12.5] ng/mL, P < .001). The calculated CIMT was also significantly higher in AS patients than in the control group (0.6 [0.3-0.9] mm vs 0.4 (0.2-0.7), P < .001]. Additionally, serum C-reactive protein level and SDC4 level were independent predictors of AS and strongly associated with CIMT. Linear regression analysis showed that serum SDC4 level was the best predictor of CIMT (P = .004). Conclusion: Our data indicate that serum SDC4 levels provide comprehensive information about the clinical activity of the disease and subclinical atherosclerosis in AS patients.